Pengaruh Model Pembelajaran Ropes (Review, Overview, Presentation, Exercise, Summary) Terhadap Hasil Belajar Akuntansi Siswa Sma Pelita Rantepao - Arisa Ranteallo; H. Abdul Rijjal; Hariany Idris (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the effect of the ROPES learning model on the accounting learning outcomes of Pelita Rantepao High School students. The variables in this research are the ROPES learning model as the independent variable and student accounting learning outcomes as the dependent variable. The population of this study was all class XI students at SMA Pelita Rantepao. The population sample was obtained from part of the population with a sample of 30 students. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing and hypothesis testing. Based on the results of hypothesis testing in this research using SPSS 28 for Windows, the results of simple linear regression analysis obtained the equation Y=13.801 + 0.759, which means that every time the ROPES Model is used, student learning outcomes increase by 0.759. The results of the Pearson product moment correlation regression analysis obtained a coefficient value of 0.759. The results of the Pearson product moment correlation regression analysis obtained a coefficient value of 0.760, meaning that theoretically between the ROPES Model variables and learning outcomes there is a strong correlation relationship. In the t-test results, a significance value of 0.001 was obtained, which is smaller than 0.05, which means that the ROPES Model variable has a significant effect on student learning outcome variables. Therefore, it can be concluded that the hypothesis proposed